FABRIC ANOMALY IN MUD CLAST DISTRIBUTION IN THE LAMBIR FORMATION (MID TO LATE MIOCENE), SARAWAK. - Padmanabhan, Eswaran (2011)
There is an increasing interest in the anisotropy of mudstone systems mainly due to seismic anisotropy caused by change in wave velocity and polarization with propagation direction. Therefore, the study was to evaluate the variability in the mud clast distribution in the heterolithic sequences present in the Lambir Formation. Mud clasts show differences in size, shape, thickness, continuity and orientation with respect to the general bedding attitude. The clasts are generally ellipsoidal in shape despite some of them being subrounded. It is evident that the amount of energy needed to transport the larger mud clasts was more than that needed to transport the finer sand grains. The origin of mud clasts remains debatable as the energy setting in which it occurs is generally not in favor of the stability of this feature. Results suggest that size variation of mud clasts with increasing distance from the base could be quite erratic in some places despite a general trend of fining upwards. We introduce the term “fabric anomaly” to describe this feature. The Lambir Formation has tremendous variability at various scales of observation. The fabric anomaly exhibited by mud clasts has the potential to impact critical properties of the clastics.